IMPLEMENTASI TEKNOLOGI TEPAT GUNA APLIKASI TRACEABILITY BERBASIS BLOCKCHAIN UNTUK TEH HIJAU DI PPTK GAMBUNG - Kastaman, Kastaman; Agung, Anak Agung Gde; Rajabi, Dhafin Rizqi; Sugiyarwi, Henokh Putri; Cahyani, Ni Putu Kanaya Putri (LPPM Universitas Bina Bangsa, 2025)
This community service program successfully implemented a blockchain-based traceability application for green tea processing at PPTK Gambung. The application integrates all stages of green tea production, from raw material reception to final product distribution, utilizing blockchain technology to ensure data security and traceability. The implementation of this system enhances the transparency of the production process and adds value to PPTK Gambung's green tea products in the international market through verifiable tracking capabilities. The use of blockchain and IPFS technology in this application has also proven effective in optimizing operational costs while maintaining data integrity. Based on the results of this implementation, the blockchain-based traceability application has the potential for broader application in the national green tea industry, providing a competitive advantage for Indonesian green tea products in the global market.